Pengaruh Innovation, Entrepreneurial Desirability, Entrepreneurial Feasibility, Terhadap Entrepreneurial Intention - Zoel Hutabarat; Irdha Helawatunisa; Ian Nurpatria Suryawan (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
The growth of small businesses pioneered by young people is currently quite large. However, the survival ability of these small businesses is still very small when compared to the new growth. This study aims to determine the effect of innovation, entrepreneurial desirability, entrepreneurial feasibility, on entrepreneurial intention. The sample of this research is Pelita Harapan University students with a total sample of 200 which is processed with Smart PLS. The results show that there is no relationship between innovation and entrepreneurial desirability, then the following results show a relationship between innovation and entrepreneurial feasibility, and there is also a relationship between entrepreneurial desirability and entrepreneurial intention, and there is also a relationship between entrepreneurial feasibility and entrepreneurial intention. This research significantly contributes to increase Entrepreneurial Intention.